Doderers Dilettantismus - Schlosser, Jan (Nordlit, 2007)
The article focuses on the function of dilettantism in the works of Austrian author Heimito von Doderer. In his poetics the "dilettant" is the negative opposite to the "artist". In the ironical novel Die erleuchteten Fenster (1951) the protagonist is an example of the classic dilettant, who plays with the world.